Armenia's path to democratization by recursive mass protests. Issue 2 (4th May 2019) - Grigoryan, Armen
ABSTRACT: This study analyses the "Velvet Revolution" of 2018 in Armenia, making a comparison with previous democratization attempts in order to facilitate understanding of some of the long-term tendencies which eventually made the revolution possible. Mass protest movements in Armenia, beginning with non-successful post-electoral protests in 2003–2004 and ending with the civil disobedience campaign resulting in regime collapse in 2018 are analyzed, and some comparisons with other cases of regime change and following developments are offered. The study contributes to the understanding of why this particular mode of regime change succeeded at that particular moment, and the implications for the post-revolution period.